TNFRSF1B Is Associated with ANCA in IBD. Issue 6 (June 2016) - Li, Dalin; Silverberg, Mark S.; Haritunians, Talin; Dubinsky, Marla C.; Landers, Carol; Stempak, Joanne M.; Milgrom, Raquel; Guo, Xiuqing; Chen, Yii-Der Ida; Rotter, Jerome I.; Taylor, Kent D.; McGovern, Dermot P. B.; et al.
Abstract : Abstract: The genetic basis of antineutrophil cytoplasmic antibody, an important biomarker of inflammatory bowel disease (IBD), has never been thoroughly examined on a genome-wide scale. In this study, we performed a 2-stage genome-wide association study (GWAS) on antineutrophil cytoplasmic antibody in IBD cases. In the 2959 IBD cases in the discovery stage, we observed an association between a variant in the gene TNFRSF1B with antineutrophil cytoplasmic antibody level (rs5745994, minor allele frequency = 0.028, beta = 18.12, 95% CI, 11.82–24.22, P = 1.89 × 10 −8 ). This association was replicated in an independent cohort of 419 IBD cases (beta = 16.91, 95% CI, 6.13–27.69, P = 2.38 × 10 −3 ). With a Q-value of 0.036, we performed a fixed-effect meta-analysis for the association of rs5745994 in both cohorts and observed a stronger association signal (beta = 17.81, 95% CI, 12.36–23.25, P = 8.97 × 10 −10 ). TNFRSF1B gene codes for tumor necrosis factor (TNF) receptor 2 (TNFR2), thereby we examined the reported TNFRSF1B variant with serum TNFR2 level. We observed a negative association with serum TNFR2 level being 8.23 EU/mL in carriers and 9.12 EU/mL in noncarriers ( P = 0.033). This finding indicates the functional role of identified TNFRSF1B variant in IBD serology and may be reflective of the underlying biological mechanisms that determine clinical expression and/or response to certain therapies. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 22 April 2016.